2012
DOI: 10.3344/kjp.2012.25.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Lidocaine on the Neuropathic Pain of Failed Back Surgery Syndrome

Abstract: BackgroundAn intravenous infusion of lidocaine has been used on numerous occasions to produce analgesia in neuropathic pain. In the cases of failed back surgery syndrom, the pain generated as result of abnormal impulse from the dorsal root ganglion and spinal cord, for instance as a result of nerve injury may be particularly sensitive to lidocaine. The aim of the present study was to identify the effects of IV lidocaine on neuropathic pain items of FBSS.MethodsThe study was a randomized, prospective, double-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…There are several studies reporting significant reduction of pain after lignocaine infusion in PDN and a variety of non-PDN conditions including fibromyalgia [41], headache [42], back pain [43], trigeminal neuralgia [44] and chronic pain syndrome [36,37]. Like previous investigations, the present study also showed a beneficial effect of lignocaine infusion to treat both PDN and non-PDN group.…”
Section: Comparison With Existing Datasupporting
confidence: 74%
“…There are several studies reporting significant reduction of pain after lignocaine infusion in PDN and a variety of non-PDN conditions including fibromyalgia [41], headache [42], back pain [43], trigeminal neuralgia [44] and chronic pain syndrome [36,37]. Like previous investigations, the present study also showed a beneficial effect of lignocaine infusion to treat both PDN and non-PDN group.…”
Section: Comparison With Existing Datasupporting
confidence: 74%
“…Such interventions should be performed by qualified specialists. Evidence-based data support the use of spinal cord stimulation [42], intrathecal drug delivery [43], intravenous infusion therapies [44,45] and sympathetic nerve blocks for the treatment of neuropathic pain. Interventional options should be used cautiously in clinical practice and reserved for patients that fail conventional therapy.…”
Section: Interventionmentioning
confidence: 98%
“…Intravenous lidocaine and ketamine infusions have been used in the treatment of neuropathic pain [44,45]. Lidocaine is a sodium channel blocker that is postulated to act centrally [59].…”
Section: Intravenous Infusion Therapiesmentioning
confidence: 99%
“…Spinal cerrahilerden sonra gelişen nöropatik ağrı ile ilgili birçok mekanizmadan bahsedilmektedir. Sinir köklerinin uzun süre bası altında kalmış olması, uygulanan cerrahi esnasında sinirlerin iyatrojenik olarak yaralanması, sinir kökleri veya dorsal kök ganglionundan çıkan ektopik impulslar nöropatik ağrıya neden olabilmektedir (9).…”
Section: Introductionunclassified